The Stigma of Widows in Jokes: An Analysis of Symbolic Violence - Syahrizal, Annisa Rachma (Riviera Publishing, 2025)
This research investigates the phenomenon of symbolic violence in language practices, focusing on the stigmatization of divorced women in Indonesian society. Employing a literature review approach, the study examines public discourse, particularly jokes made by political figures specifically former gubernatorial candidate pairs in Indonesia’s 2024 regional election that perpetuate harmful stereotypes. Through an analysis of news coverage, scholarly literature, and relevant theoretical frameworks, the study explores how patriarchal structures normalize derogatory language and social stigma toward divorced women. The findings suggest that such symbolic violence is deeply embedded in everyday communication and is reinforced by figures in positions of power, contributing to the marginalization of women who do not conform to traditional marital expectations. This research aims to advance critical discourse on gender, language, and social power by highlighting the subtle yet impactful ways language perpetuates gender inequality. The study's implications underscore the need for greater sensitivity in public language use and call for educational interventions to challenge and transform discriminatory narratives